Improvement of penicillin G acylase expression in Escherichia coli through UV induced mutations - Arshad,Rubina (2010)
We used ultraviolet (UV) radiation to induce mutation in three locally isolated strains of Escherichia coli. Different dilutions of bacterial cultures were exposed to UV lamp of 254 nm wavelength for different time intervals at varied distances ranging from 5 to 210 sec and 5 to 100 cm. Viable colonies were screened for mutants with an increased production of penicillin G acylase (PGA) and a reduced production of β-lactamase, which are the desired properties of PGA producing industrial strains. A survival curve was made to get optimum exposure time and distance. The survival percentage for each exposure period was calculated and 1-5% survival was found useful for obtaining mutants with desired change. Screening for PGA and β-lactamase constitutive and/or deficient mutants was made by Serratia marcescens overlay test. A total of 100 survivors were selected of which 49% expressed PGA activity higher than the parent strain. Frequency of β-lactamase constitutive and deficient mutants was 48 and 52%, respectively. The best hyper-producing mutant (BDCS-N-M74), with almost negligible expression of β-lactamase, exhibited three-fold (22.5 mg 6-APA h-1 mg-1 wet cells) increase in PGA activity compared with that in the parent strain (6.7 mg 6-APA h-1 mg-1 wet cells). The results indicated the successful induction of UV mediated mutation in E. coli for PGA hyper-producing mutants lacking β-lactamase activity.